THE IMPACT OF COMPETENCE AND ORGANIZATIONAL COMMITMENT EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHF BEHAVIOR AS INTERVENING - Syafitri, Sulistiani; Nurwati; Mahrani, Sri Wiyati; Alam, Ryan Saputra (Scientia Integritas Utama, 2023)
The purpose of this study is to: (1) Analyze the effect of competence on employee performance; (2) Examine the influence of organizational commitment on employee performance; (3) Investigate how competence affects organizational citizenship behavior (OCB); (4) Assess the effect of organizational commitment on OCB; (5) Evaluate the impact of OCB on employee performance; (6) Investigate the effect of competence on employee performance with OCB as a mediating variable; (7) Analyze the effect of organizational commitment on employee performance through OCB as an intervening variable. The study focuses on the population of 43 permanent employees at the Electricity Company in Kendari City. Since the population is fewer than 100, all permanent employees were selected as respondents. Data analysis was conducted using the Partial Least Square (PLS) methodology. Based on the findings, the researcher recommends using OCB as a mediator between competence and employee performance at the Electricity Company in Kendari City and encourages the continued use of OCB as a mediator in the relationship between competence and employee performance.